Analisis Faktor-Faktor Penentu Tata Kelola Pemerintahan Di Pemerintah Kota Surabaya Periode Kepemimpinan Tri Risma Harini Tahun 2015-2020 - Muhammad Quranul Kariem; Noor Ishmatuddin (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2021)
The Surabaya City Government under the leadership of Tri Risma Harini in the 2015-2020 period has shown various successes with indicators from the economic, development, and environmental sectors. The research method used in this study is a qualitative descriptive method with a literature review approach. The results showed that several internal and external factors of government greatly influenced the development of good governance, which had an impact on the success of governance.